Transfer of Natural Radionuclides in Terrestrial Food Chains : A Review of Investigations in Finland - Salminen-Paatero, Susanna; Paatero, Jussi (Multidisciplinary Digital Publishing Institute, 2021)
Transfer of natural radionuclides 210 Pb, 210 Po, 238 U, and 228,230,232 Th in subarctic food chains has been studied in Finland since the 1960s. The unique food chain lichen-reindeer-man related to Sami people in Finnish Lapland and other food chain options, from berries or mushrooms to man, have been explored and the activity concentrations of natural radionuclides in biological samples determined. The results from Finnish radioecological studies are summarized and differences in bioaccumulation between different radionuclides are discussed. It was found out that, although a substantial amount of activity concentration data exist from the research projects executed in Finland during the last 6 decades, more data, especially from U and Th, in biological environment and humans would be useful, e.g., for modeling purposes and for improved assessment of bioaccumulation and adverse effects (both radiological and chemical) of radionuclides.